Discrete Logistic Exponential Distribution with Application - Afrah Al-Bossly; M. S Eliwa; Muhammad Ahsan-Ul-Haq; Mahmoud El-morshedy (Statistics, Optimization & Information Computing, 2023)
In this paper, a new two-parameter discrete logistic exponential distribution is proposed based on the survival discretization approach. Some statistical properties are derived, and it is found that the proposed model can be used to discuss several kinds of failure rates including unimodal, bathtub, and increasing-shaped. Moreover, it can be utilized effectively to model under- and over-dispersed data. The distribution parameters are estimated using the maximum likelihood technique. The behavior of maximum likelihood estimators is assessed utilizing a comprehensive simulation study. In the end, two real data are analyzed to show the usefulness of the new discrete distribution.